In the company of others: social factors alter acute alcohol effects - Kirkpatrick, Matthew G.; de Wit, Harriet (Psychopharmacology, 2013)
Rationale Alcohol is usually consumed in social contexts. However, the drug has been studied mainly under socially isolated conditions, and our understanding of how social setting affects response to alcohol is limited. Objectives The current study compared the subjective, physiological, and behavioral effects of a moderate dose of alcohol in moderate social drinkers who were tested in either a social or an isolated context and in the presence of others who had or had not consumed alcohol. Methods Healthy men and women were randomly assigned to either a social group tested in pairs (SOC; N = 24), or an isolated group tested individually (ISO; N = 20). They participated in four sessions, in which they received oral alcohol (0.8 g/kg) or placebo on two sessions each, in quasi-randomized order under double-blind conditions. In the SOC condition, the drug conditions of the co-participants were varied systematically: on two sessions, both participants received the same substance (placebo or alcohol) and on the other two sessions one received alcohol while the other received placebo. Cardiovascular measures, breath alcohol levels, and mood were assessed at regular intervals, and measures of social interaction were obtained in the SOC group. Results Alcohol produced greater effects on certain subjective measures in the SOC condition compared with the ISO condition, including feelings of intoxication and stimulation, but not on other measures such as feeling sedated or high, or on cardiovascular measures. Within the SOC condition, participants rated themselves as more intoxicated when their partner received alcohol, and paired subjects interacted more when at least one participant received alcohol. Conclusions The presence of others enhances some of the subjective and behavioral effects of alcohol, especially the presence of another intoxicated individual. This enhancement of alcohol effects may explain, in part, why it is used in a social context.